Embodiment and education: the body and the new paradigms of complexity - Ahlert, Alvori (2011)
This paper discusses the issues of embodiment and education in the context of interdisciplinary teaching among teachers of Physical Education and Natural Sciences, presented in a lecture at the National Meeting of Teachers of Physical Education and Natural Science Education Network Synod. First, the concepts of education and embodiment are introduced. Based on these concepts, the issues of embodiment in the context of the paradigms of complexity and communicative action are addressed. The discussion concludes with the presentation of challenges for interdisciplinary work among teachers of Physical Education and Natural Sciences on the issue of corporality at school.